User Experience Analysis in Website-Based Digital Invitation Design - Suksmawati, affi Nizar; Peldon, Tshering (Journal of Information Technology application in Education, Economy, Health and Agriculture, 2024)
Human-Computer Interaction (HCI) studies how humans interact with computer technology, focusing on interface design that allows users to communicate and operate computer systems effectively and intuitively. The goal is to enhance user experience, productivity, and satisfaction through approaches that consider users' needs, preferences, and abilities. A digital invitation is created digitally, usually in electronic formats such as email, text messages, social media posts, or websites. Digital invitations can be images or text sent to guests via digital platforms, often accompanied by RSVP links or additional information. Creating and using digital invitations addresses various limitations of traditional physical invitations, such as accessibility issues, delivery costs and time, and environmental impact. This research involves creating a prototype of a digital invitation using design platforms like Canva and collecting and analyzing online questionnaire data to assess user efficiency, flexibility, and satisfaction. The results show that digital invitations have many advantages, including cost efficiency, reduced environmental impact, ease of management, and higher interactivity than physical invitations. The conclusion of this study emphasizes the importance of interactive and user-friendly design, as well as high user satisfaction with digital invitations. Recommendations include further development of interactive features, enhanced data security, testing on various devices, and promotion and education on the benefits of digital invitations.